Localization of premature ventricular contractions from the papillary muscles using the standard 12-lead electrocardiogram: a feasibility study using a novel cardiac isochrone positioning system. (23rd December 2016) - van Dam, Peter M.; Boyle, Noel G.; Laks, Michael M.; Tung, Roderick
Abstract : Aims: The precise localization of the site of origin of a premature ventricular contraction (PVC) prior to ablation can facilitate the planning and execution of the electrophysiological procedure. In clinical practice, the targeted ablation site is estimated from the standard 12-lead ECG. The accuracy of this qualitative estimation has limitations, particularly in the localization of PVCs originating from the papillary muscles. Clinical available electrocardiographic imaging (ECGi) techniques that incorporate patient-specific anatomy may improve the localization of these PVCs, but require body surface maps with greater specificity for the epicardium. The purpose of this report is to demonstrate that a novel cardiac isochrone positioning system (CIPS) program can accurately detect the specific location of the PVC on the papillary muscle using only a 12-lead ECG. Methods and results: Cardiac isochrone positioning system uses three components: (i) endocardial and epicardial cardiac anatomy and torso geometry derived from MRI, (ii) the patient-specific electrode positions derived from an MRI model registered 3D image, and (iii) the 12-lead ECG. CIPS localizes the PVC origin by matching the anatomical isochrone vector with the ECG vector. The predicted PVC origin was compared with the site of successful ablation or stimulation. Three patients who underwent electrophysiological mapping and ablation of PVCs originating from the papillary muscles were studied. CIPS localized the PVC origin for all three patients to the correct papillary muscle and specifically to the base, mid, or apical region. Conclusion: A simplified form of ECGi utilizing only 12 standard electrocardiographic leads may facilitate accurate localization of the origin of papillary muscle PVCs.